A Correlational Study of Non-Mediating Mothers of Preschooler: Is Mindful Parenting Associated with Child Resilience? - Putri, Ainama Nafisa; Muthmainah (Universitas Pendidikan Ganesha, 2024)
There is some evidence that mindful parenting is a parenting approach that involves parents in adolescent behaviour. However, only a few studies have investigated the relationship between mindful parenting to early childhood resilience. This research aims to analyze the relationship between mindful parenting and early childhood resilience through a non-mediation correlation study. The method used is regression analysis with the cluster sampling technique. The research sample consisted of 135 mothers who had young children. The mindful parenting research instrument uses the IM-P scale, and resilience uses the RMS-25 scale, which has been adapted according to research needs. The instrument was declared valid and reliable with a Cronbach alpha value greater than 0.6, namely 0.904 for mindful parenting and 0.951 for resilience. The research results show that mindful parenting is positively correlated with children's resilience. This is proven by the significance value (0.000 greater than 0.05) and the coefficient of determination value of 41.4%, and the rest is influenced by other variables that were not researched. Mindful parenting fosters children's resilience so that it can build the ability to manage emotions, make decisions, identify problems, and respect oneself and others.